An e-government adoption framework for developing countries: a case study from Sudan - Abdalla, Sara (Cranfield University, 2012)
Over the past decade, rapid progress in ICT has encouraged many governments to incorporate new technology into their national economic development strategies. Egovernment is an important application within ICT and has become more significant in the agenda of policy and decision makers the world over. E-government created a new medium that changed the nature of the whole public sector and its relationship with its constituencies. It has had a profound effect on various socioeconomic and political aspects of society. E-government provides delivery of public services in a much more convenient and cost-effective way, offering huge opportunities to improve public sector efficiency. However, the process of change also gives rise to new challenges and difficulties, especially in developing countries, where many initiatives have not been successful. This is as a result of the massive deficiencies in basic infrastructure, human capacity and financial resources, along with the attendant political and cultural constraints. These factors are crucial and impede the adoption of egovernment and the building of an information based society and economy. Egovernment initiatives must therefore account for the specific government systems, technological infrastructure and environmental conditions of the host country. Many of the models and frameworks built to assist in the adoption process in developing countries have been adapted from e-government implementation experiences in Western developed countries. While there are important lessons to be learnt, these frameworks have limited application in Africa and developing countries in other regions. Previously it was difficult to investigate e-government in developing countries due to their low levels of development. Recent advances in e-government in these countries have made it possible to conduct studies and analyse their experiences and practices. This research empirically examined the adoption of e-government at a national and organisational level, taking the public sector in Sudan as a case study. A qualitative approach was followed and data was collected from Sudan using interviews with key officials and top managers; supported by published documents in the public domain.The data was analysed using content analysis and the results verified with experts from a Sudanese public organisation. The findings of the research contributed to the identification of the critical factors in Sudan, and to the development of an e-government adoption framework. The framework combines elements from the Technological, Organisational and Environmental (TOE) model; guiding decision makers to better manage issues related to the adoption process regarding the development of the technical infrastructure, management systems, values and strategies. The use of the proposed framework can help integrate e-government into the public sector in order to accelerate social and economic progress in developing countries.
Keywords: Critical factors; public sector; technology; organisation; environment; TOE model